Taxonomic and landscape-use composition of planted vegetation across a tropical university campus in Central Java, Indonesia - FADIA AULIANISSA AINAYA; NUR ROHMAYANI ANGGELIKA PUTRI; DANASTRI NUR ATHAYA RADYA PUTRI; AIKO YHOVIERA FARRAZ MU'ALI; SESILIA RETNO AYU NINGTYAS; HERLINA NOFITASARI; AHMAD DWI SETYAWAN (Nusantara Bioscience, 2026)
Abstract. Ainaya FA, Putri NRA, Putri DNAR, Mu'ali AYF, Ningtyas SRA, Nofitasari H, Setyawan AD. 2026. Taxonomic and landscape-use composition of planted vegetation across a tropical university campus in Central Java, Indonesia. Nusantara Bioscience 18 (1): n180110. https://doi.org/10.13057/nusbiosci/n180110. Urban university campuses are intensively managed landscapes that can retain diverse planted floras and support long-term biodiversity planning. This study produced a traceable inventory of planted vegetation at the main campus of Universitas Sebelas Maret, Surakarta, Central Java, Indonesia. Seventeen sampling stations were distributed purposively among ten campus landscape zones; each station comprised four nested component plots assigned to tree, pole, sapling, and seedling/low-stature classes, giving 68 component plots rather than 68 independent sampling units. The archived checklist was audited at the taxon level, and every entry was assigned to one mutually exclusive primary landscape-use category. The inventory contained 99 operational taxonomic entries representing 98 named species because two cultivated forms of Psidium guajava were retained separately; entries belonged to 39 families. Fabaceae was the richest family (17 entries), followed by Arecaceae and Myrtaceae (seven each). Ornamental plants were the largest use category (37 entries; 37.4%), followed by fruit trees (27; 27.3%), shade trees (19; 19.2%), timber species (6; 6.1%), multipurpose plants (6; 6.1%), and medicinal plants (4; 4.0%). Across structural classes, 61 taxa occurred in the seedling/low-stature class, 28 in sapling, 28 in pole, and 32 in tree classes; entries could occur in multiple classes. Sixty-five entries (65.7%) were represented in only one class, whereas five (5.1%) occurred in all four; ornamental entries were concentrated in the seedling/low-stature class. Because plot-level abundance, DBH data, vouchers, and repeated surveys were unavailable, abundance-based diversity, regeneration, sector comparisons, and ecosystem-service estimates could not be validated. The audited inventory provides a reproducible baseline for future georeferenced, abundance-based, and temporal campus vegetation monitoring.